Elektronik yöntemler ile üretilen tifdruk baskı kalıplarının incelenmesi - Hashemi Moghaddam, Seyedeh Nasrin (My University, 2005)
ELEKTRONİK YÖNTEMLER İLE ÜRETİLEN TİFDRUK KALIPLARININ İNCELENMESİ Matbaa sektöründe, ambalaj dünyasının büyük bir payı olan Tifdruk baskı sisteminin vazgeçilmez olduğu görülmektedir. Ambalajın büyük bir kısmı Tifdruk baskı sistemi ile yapılmaktadır ve matbaacılıktaki teknolojik gelişmeler ile birlikte bu baskı sistemi de gelişmektedir. Bu çalışmada, genel olarak dünyada ve ülkemizde yoğun bir şekilde kullanılan Tifdruk baskı sisteminde kullanılan konvansiyonel emülsiyonlu ve diğer elektronik yöntemler ile üretilen kalıplardan bahsedildi. Değişik yöntemlerle hazırlanan bu kalıpların hazırlanış prosesleri incelenerek elmas uç ve lazer uç yöntemleri ile elde edilen kalıpların diğer yöntemlerle elde edenlere oranla avantajları araştırıldı. Kullanılan yeni sistemler için tasarlanan yeni programlar, kullanım alanları ve avantajları, yabancı kaynaklar kullanarak incelendi. Görüntünün bilgisayardan kalıba aktarımı için tasarlanan programların özellikleri irdelendi. Tramların şekilleri, sıklığı ve görüntünün aktarılmasındaki öneminden bahsedildi. Eski ve yeni gravür silindiri kazıma yöntemleri ile incelendi. Avantajları, hız ve kalitesi, görüntünün aktarılması ve çalışma prensipleri anlatıldı. Konvansiyonel ve yeni yöntemler ile hazırlanan kalıplarla yapılan baskı örnekleri değerlendirildi. Ocak, 2005 Seyedeh Nasrin HASHEMI MOGHADDAM

EXAMINING TIFDRUK PLATE WHICH ARE PRODUCED BY USING ELECTRONICAL METHODS In printing sector, especially in the world of packaging, we all see that there is an undeniable usage of Tifdruk printing method. The large part of packing is completed by using this system. At the same time, there has been recent technological developments utilizing this method in this sector. In this particular study, the plate which are produced with conventional emulsion and using other electronical methods are also observed in Tifdruk printing system. This method is commonly used in Turkey as well as in the rest of the world. In addition, the advantages and the disadvantages of using either diamond or lazer needles have been searched on the process of using these plate with the preparation of different methods. The most recent designed software and/ or hardware systems, the key elements of their usage and their advantages and disadvantages have been researched using outside foreign sources. Also, the qualities of these designed pograms have been observed in detail at the time of transferring these images from the computer into the moulds. In this paper, the shape of the trams, its frequency, and the importance of the transferring images are underlined very carefully. The process of removal system from the cylinders of old and new gravures have also been observed. The key benefits, their speed and quality, image transfer as well as their working principals are also identified. The different prepress examples of the moulds which are prepared using the old and/ or the new methods have also been evaluated in this study. Ocak, 2005 Seyedeh Nasrin HASHEMI MOGHADDAM
Keywords: Matbaa Eğitimi